2021
DOI: 10.1136/bmjopen-2021-053216
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and disease experience in patients with heart failure with reduced ejection fraction in Spain: a mixed-methods study

Abstract: ObjectivesTo gather insights on the disease experience of patients with heart failure (HF) with reduced ejection fraction (HFrEF), and assess how patients’ experiences and narratives related to the disease complement data collected through standardised patient-reported outcome measures (PROMs). Also, to explore new ways of evaluating the burden experienced by patients and caregivers.DesignObservational, descriptive, multicentre, cross-sectional, mixed-methods study.SettingSecondary care, patient’s homes.Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Previous reports in heart failure patients have also documented association between NYHA and KCCQ as well as between NYHA and EQ‐5D‐5L. 33 , 43 , 44 , 45 To our knowledge, the Nordic PROACT study is the first to investigate correlations between NAC staging and different HRQoL measures.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous reports in heart failure patients have also documented association between NYHA and KCCQ as well as between NYHA and EQ‐5D‐5L. 33 , 43 , 44 , 45 To our knowledge, the Nordic PROACT study is the first to investigate correlations between NAC staging and different HRQoL measures.…”
Section: Discussionmentioning
confidence: 84%
“…Previous reports in heart failure patients have also documented association between NYHA and KCCQ as well as between NYHA and EQ-5D-5L. 33,[43][44][45] To our knowledge, the Nordic PROACT study is the first to investigate correlations between NAC staging and different HRQoL measures. Though both methods of classifying disease severity correlated well to the analysed PROMs, NYHA classes showed a stronger correlation than NAC stages, in that the correlation between NYHA classes and the individual PROMs stayed significant after Bonferroni correction.…”
Section: MDImentioning
confidence: 83%
“…The same was true for many data on baseline patient characteristics and outcome parameters. Many studies from our analysis did not include or report data on patient’s functional heart failure status (e.g., NYHA class) or LV function although these factors already have been proven extensively to have a large impact on quality of life [ 79 , 80 ]. However, many of the included trials either showed data on medical outcome (improvement of functional NYHA class, improvement of measured LV function) or parameters of psychological well-being (quality of life, mental diseases).…”
Section: Discussionmentioning
confidence: 99%
“…HF is a long-term debilitating disease that severely affects the quality of life by the need for hospitalizations, reduced ability to undertake daily living activities, and disturbed psychosocial well-being. The limitations in patients with HF may be even more expressed compared to those with other chronic conditions such as diabetes, cancer, or Alzheimer’s disease [ 47 ]. This may have translated into lower satisfaction with healthcare in HF patients.…”
Section: Discussionmentioning
confidence: 99%